iOverheid - Wetenschappelijke Raad voor het Regeringsbele (WRR Rapporten, 2011)
How does the use of ict affect the relationship between government and its citizens? This book analyses the developments of networking information and concludes that in everyday practice an iGovernment has gradually come into existence, overtaking the old paradigm of the eGoverment. The iGoverment, effectively running at full speed on information flows and networks, is however seriously out of step with the self-image of the digital government, and the existing structure and division of responsibilities. This book is based on the report on iGovernment that the Scientific Council for Government Policy (WRR) presented to the Dutch Government in March 2011. "This book contributes powerfully to the understanding and evaluation of the development - beyond 'eGovernment' - of 'information Government', centred on highly complex flows and uses of information for public services, care and control, rather than technology itself. Sound empirical research and a concern to create better governance of iGovernment enable the authors to bring a sharply critical eye to their call for greater awareness by policy-makers, and for a strategic, reasoned and institutionalised relationship among the principles involved. These include ones that are often neglected: privacy, freedom of choice, accountability and transparency. Their recommendations are important, not only for the Netherlands". Charles D. Raab, Professor Emeritus and Honorary Professorial Fellow, University of Edinburgh "This book will be a valuable resource for researchers and scholars seeking to understand the possibilities, dilemmas and challenges of bringing the Internet and related technologies to centre stage in government and public services. It offers a fascinating case study of electronic government and 'information government' in the Netherlands, with examples from local, national and eu government, a wide-ranging literature review and a number of recommendations as to how iGovernment should develop". Helen Margetts, Professor of Society and the Internet and director of the Oxford Internet Institute, University of Oxford "Not only does this book offer an insightful analysis of the problems that ongoing digitization poses for citizens and the goverrnment itself (such as creeping loss of data quality), it also places highly valuable markers for the decisions that must be taken on the challenging path that lies ahead for iGovernment, in providing a new model for weighing up the various fundamental interests at stake". Alex Brenninkmeijer, National Ombudsman, The Netherlands